STUDENTS’ READINESS IN USING TECHNOLOGY DURING COVID-19 PANDEMIC - Marta Widiawitasari Br Simamora; Achmad Yudi Wahyudin; Alvi Raihan Utami (Universitas Teknokrat Indonesia, 2022)
To prevent the spread of Covid-19, online learning or LFF is implemented. LFH shifted formal education practice from the classroom (on-site) learning to online learning. All subjects in schools are conducted online, including English subjects. One of the software applications that can assist in English teaching and learning online was Learning Management Systems. One LMS that can be used as a learning platform is Moodle. The friendly tools that Moodle offers help students to adapt quickly to this platform. However, with this sudden shifting between offline to online environments, the students need to adjust without maximum preparation. Therefore, in implementing Moodle, the teachers should know students' readiness and perception of using Moodle as an English learning media. In this research, the researchers apply survey research that explores students' readiness and perceptions towards the use of Moodle in learning English during the pandemic Covid-19. The instrument uses the questionnaire, and the participants are 100 students of SMK Yadika Bandarlampung. The result of this research shows that students of SMK Yadika Bandarlampung are ready to implement Moodle as their English learning media. They also had a positive perception toward Moodle during their time using Moodle. However, the students still face some problems such as connection and internet data, which often becomes a barrier for them in following Moodle activities.